ANALISIS PERBANDINGAN KESEJAHTERAAN PETANI KARET (Hevea bransiliensis) DAN PETANI SAWIT (Elaeis guineensis) DI DESA DURIAN BUNGKUK KECAMATAN BATU AMPAR - Dewi, Nurul Mellyana; Naparin, Muhammad; Rezekiah, Arfa Agustina (Jurnal Hutan Tropis, 2024)
The welfare of farmers has an impact on poverty levels, food security and economic stability in a country. Welfare is a situation where a citizen feels that their situation has been well met for all their needs both materially, spiritually and socially. The aim of this research is firstly to compare the welfare of the community of rubber farmers and palm oil farmers in Durian Bungkuk Village, Batu Ampar District and secondly, to analyze the types of farmers that have an impact on the welfare of the people of Durian Bungkuk Village, Batu Ampar District. This research uses three sustainable welfare variables, namely income/economy, education and health. This research uses a quantitative method by determining respondents using the census method. Management of this data analysis uses homogeneity tests, normality tests and independent t-tests with the SPSS 25 application. Analysis of the types of farmers who provide more prosperity uses the largest average data of respondents' answers from the Likert Scale. The homogeneity test results obtained a significance value of 0.717. The normality test results showed that the significance value for rubber farmers was 0.124, while the significance value for oil palm farmers was 0.082. The results of the independent t-test between rubber farmers and oil palm farmers obtained a significant value (2-tailed) of 0.000, meaning that there is a difference in the average income of rubber and oil palm farmers. The average result per variable and the average respondent's answer was that the rubber farmer's yield was 3.55 while the palm oil farmer's yield was 3.15, so that rubber farmers provided more welfare than palm oil farmers for the community in Durian Bungkuk village, Batu Ampar district.